Geomorphic change in the Ganges-Brahmaputra-Meghna Delta - Paszkowski, A; Goodbred, S; Borgomeo, E; Khan, MSA; Hall, JW (Springer Nature, 2021)
More than 70% of large deltas are under threat from rising sea levels, subsidence and anthropogenic interferences, including the Ganges–Brahmaputra–Meghna (GBM) delta, the Earth’s largest and most populous delta system. The dynamic geomorphology of this delta is often overlooked in assessments of its vulnerability; consequently, development plans and previous management investments have been undermined by unanticipated geomorphic responses. In this Review, we describe GBM delta dynamics, examining these changes through the Drivers–Pressures–States–Impacts–Responses framework. Since the early Holocene, the GBM delta has evolved in response to a combination of tectonics, geology, changing river discharge and sea level rise, but the dynamics observed today are driven by a complex interplay of anthropogenic interferences and natural background processes. Contemporary geomorphic processes such as shoreline change, channel migration, sedimentation and subsidence can increase flooding and erosion, impacting biodiversity, ground and water contamination and local community livelihoods. Continued human disturbances to the GBM delta, such as curtailing sediment supplies, modifying channels and changing land use, could have a more direct influence on the future geomorphic balance of the delta than anthropogenic climate change and sea level rise. In order to contribute to long-term delta sustainability, adaptation responses must therefore be informed by an understanding of geomorphic processes, requiring increased transdisciplinary research on future delta dynamics at centennial timescales and collaboration across all governing bodies and stakeholders.